Differential structure and functional gene response to geochemistry associated with the suspended and attached shallow aquifer microbiomes from the Illinois Basin, IL. (1st September 2021) - Dong, Yiran; Sanford, Robert A.; Connor, Lynn; Chee-Sanford, Joanne; Wimmer, Bracken T.; Iranmanesh, Abbas; Shi, Liang; Krapac, Ivan G.; Locke, Randall A.; Shao, Hongbo
Highlights: Use of multiple gene amplicons to understand aquifer microbiomes. Distinct spatiotemporal changes occur in suspended and attached microbial communities. Each functional gene community exhibits unique spatiotemporal changes. Different ecological processes control community and functional gene assembly. Abstract: Despite the clear ecological significance of the microbiomes inhabiting groundwater and connected ecosystems, our current understanding of their habitats, functionality, and the ecological processes controlling their assembly have been limited. In this study, an efficient pipeline combining geochemistry, high-throughput Fluidigm TM functional gene amplification and sequencing was developed to analyze the suspended and attached microbial communities inhabiting five groundwater monitoring wells in the Illinois Basin, USA. The dominant taxa in the suspended and the attached microbial communities exhibited significantly different spatial and temporal changes in both alpha- and beta-diversity. Further analyses of representative functional genes affiliated with N2 fixation ( nifH ), methane oxidation ( pmoA ), and sulfate reduction ( dsrB, and aprA ), suggested functional redundancy within the shallow aquifer microbiomes. While more diversified functional gene taxa were observed for the suspended microbial communities than the attached ones except for pmoA, different levels of changes over time and space were observed between these functional genes. Notably, deterministic and stochastic ecological processes shaped the assembly of microbial communities and functional gene reservoirs differently. While homogenous selection was the prevailing process controlling assembly of microbial communities, the neutral processes (e.g., dispersal limitation, drift and others) were more important for the functional genes. The results suggest complex and changing shallow aquifer microbiomes, whose functionality and assembly vary even between the spatially proximate habitats and fractions. This research underscored the importance to include all the interface components for a more holistic understanding of the biogeochemical processes in aquifer ecosystems, which is also instructive for practical applications. Graphical abstract: Image, graphical abstract